2023
DOI: 10.1111/brv.12999
|View full text |Cite
|
Sign up to set email alerts
|

Chasing footprints in time – reframing our understanding of human foot function in the context of current evidence and emerging insights

Anja‐Verena Behling,
Michael J. Rainbow,
Lauren Welte
et al.

Abstract: In this narrative review we evaluate foundational biomechanical theories of human foot function in light of new data acquired with technology that was not available to early researchers. The formulation and perpetuation of early theories about foot function largely involved scientists who were medically trained with an interest in palaeoanthropology, driven by a desire to understand human foot pathologies. Early observations of people with flat feet and foot pain were analogized to those of our primate ancesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…Dissecting the foot into isolated components might also, as cautioned by Gould & Lewontin [28], result in looking for and proposing form-function relationships where none exists. Furthermore, Behling et al [29], in their comprehensive review of the literature on human foot function to date, assert that evidence supporting theories of the foot acting as a mobile adaptor and rigid lever (centred around the MLA) is poor at best. Consequently, they, along with several others [30][31][32], advocate acknowledging the structural complexity and functional versatility of our feet.…”
Section: Introductionmentioning
confidence: 99%
“…Dissecting the foot into isolated components might also, as cautioned by Gould & Lewontin [28], result in looking for and proposing form-function relationships where none exists. Furthermore, Behling et al [29], in their comprehensive review of the literature on human foot function to date, assert that evidence supporting theories of the foot acting as a mobile adaptor and rigid lever (centred around the MLA) is poor at best. Consequently, they, along with several others [30][31][32], advocate acknowledging the structural complexity and functional versatility of our feet.…”
Section: Introductionmentioning
confidence: 99%
“…The human hindfoot complex is unique in shape compared to other non-human primates with specific adaptations to enable habitual upright locomotion (10)(11)(12). Compared to nonhuman primates, the human calcaneus is larger and more robust, presumably to accommodate increased ground reaction forces, and muscular forces applied by the Achilles tendon (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…However, quantifying in vivo midtarsal and subtalar joint motion is challenging. The rare data that has been captured has often been used to test the incorrect assumption that the foot becomes rigid during push-off [6][7][8][9], which is still a common misconception of foot function. It was previously suggested that the large variation in bone shape has the potential to modify midtarsal complex and subtalar joint function [10][11][12][13].We propose to investigate the function of the midtarsal complex and subtalar joint under a more modern framework that views the foot as a highly mobile structure [6], while accounting for the underlying morphology.…”
Section: Introductionmentioning
confidence: 99%